The Trifluoromethyl Sulfinyl and Oxathiyl Radicals. Issue 7 (16th November 2017) - Wu, Zhuang; Xu, Jian; Deng, Guohai; Chu, Xianxu; Sokolenko, Liubov; Trabelsi, Tarek; Francisco, Joseph S.; Eckhardt, André K.; Schreiner, Peter R.; Zeng, Xiaoqing
Abstract: Two hitherto unreported sulfur‐centered radicals CF3 SO . and CF3 OS . were generated in the gas phase through high‐vacuum flash pyrolyses of sulfoxide CF3 S(O)X (X=CF3, Cl, PhO) precursors. The CF3 OS . molecule is the first experimental example that constitutes an oxathiyl radical. It was isolated and characterized by combining matrix‐isolation IR and UV/Vis spectroscopy with quantum chemical computations up to the UCCSD(T)‐F12/cc‐pVTZ‐F12 level of theory. Upon UV light irradiation (254 or 266 nm), sulfinyl radical (CF3 SO . ) isomerizes to oxathiyl radical (CF3 OS . ) in cryogenic noble gas matrices (Ar and Ne). Natural population analyses at the BP86/def2‐TZVPP//UCCSD(T)‐F12/cc‐pVTZ‐F12 level suggest that the spin density in CF3 OS . is mainly localized on the sulfur atom (0.86), whereas, in CF3 SO . the spin density is almost equally distributed on the sulfur (0.55) and oxygen (0.43) atoms. Abstract : The hitherto unknown oxathiyl radical CF3 OS . was generated through either thermal or photolytic isomerization of the sulfinyl radical CF3 SO . . Both radicals were characterized for the first time by combining matrix‐isolation IR and UV/Vis spectroscopy with quantum chemical computations.